The future of education : reimagining our schools from the ground up - Egan, Kieran (Yale University Press, 2008)
This engaging book presents a frontal attack on current forms of schooling and a radical rethinking of the whole education process. Kieran Egan, a prize-winning scholar and innovative thinker, does not rail against teachers, administrators, or politicians.